Parhyale plumicornis (Crustacea: Amphipoda: Hyalidae): is this an anti-lessepsian Mediterranean species? Morphological remarks, molecular markers and ecological notes as tools for future records. Issue 3 (4th May 2017) - Iaciofano, Davide; Lo brutto, Sabrina
Abstract : Hyalid amphipods living in coastal marine habitats are frequently included in ecological studies. The systematics of this taxon has been subject to profound changes, with an emphasis on the North Pacific fauna. Since a proper species delimitation is a prerequisite in taxonomic and ecological studies, Parhyale plumicornis (Heller, 1866) has been herein re-described, showing the criticisms and mismatches of various characters, which were previously used in dichotomous keys. This species was collected for the first time off the western coast of Sicily Island (Italy: central Mediterranean Sea). The male is peculiar, due to the second antennae heavily setose posteriorly and bearing long tufts of plumose ventral setae. In this paper, the species will be illustrated, and morphological polymorphism, molecular tags and ecological features will be reported. The species does not appear to be frequent in the Mediterranean Sea but it is important that marine biologists identify it accurately. A recent record, possibly ascribable to Parhyale plumicornis in the Red Sea, could indicate that this species is the first anti-lessepsian amphipod, which has migrated from the Mediterranean Sea towards the Red Sea. http://www.zoobank.org/urn:lsid:zoobank.org:pub:770BEDA1-3E06-464F-9D34-8AFE43592FCA